Correlation of Obesity with External Cephalic Version Success among Women with One Previous Cesarean Delivery - Rodney McLaren Jr; Fouad Atallah; Nelli Fisher; Howard Minkoff (Thieme Medical Publishers, Inc., 2020)
Objective Our aim was to assess the correlation of body mass index (BMI) with the success rate of external cephalic version (ECV) among women with one prior cesarean delivery. Study Design A cross-sectional study of pregnant women with one previous cesarean delivery who underwent ECV. The relationship between BMI and success rate of ECV was assessed. Adverse outcomes were also compared between women with an ECV attempt, and women who had a repeat cesarean delivery. Data were extracted from the U.S. Natality Database from 2014 to 2017. Pearson's correlation coefficient was performed to assess the relationship between BMI and success rate of ECV. Results There were 2,329 women with prior cesarean delivery underwent an ECV attempt. The success rate of ECV among the entire cohort was 68.3%. There was no correlation between BMI and success rate of ECV (r = 0.024, p = 0.239). Risks of adverse maternal and neonatal outcomes were similar between the ECV attempt group and the repeat cesarean delivery group. Conclusion There was no correlation of BMI with the rate of successful ECV among women with one prior cesarean delivery. Given the similar success rates of ECV and adverse outcomes, obese women with one prior cesarean delivery should be offered ECV.